Regeneração natural e relações ambientais em um remanescente de floresta estacional decidual no Parque Estadual do Pau Furado, Uberlândia, MG - Silva, Pedro Paulo Ferreira (2011)
The aim of the present paper was to investigate natural regeneration of an arboreal community and the influence of environmental and canopy variables on species density and distribution along a deciduous forest remnant in the Triangulo Mineiro, region, MG. We elaborated a general introduction, in which aspects of biodiversity loss due to human actions (deforestation, agriculture) are discussed and the importance of different physiognomies in the Brazilian cerrado, especially deciduous forests, are pointed out. Following this theoretical background, we present two chapters. The first one discusses a survey of arboreal natural regeneration carried out in random plots subdivided into two sampling classes. We calculated species density, frequency and the mean number of species and individuals per plot. An ordination analysis of species according to density was performed, and we also constructed rarefaction curves based on nonparametric estimators. Natural regeneration for both sampling classes was very similar in number of species to other deciduous forests, with Adadenanthera colubrina as the dominant species, indicating a high regeneration and silvicultural potential. Nonparametric estimators presented differences among them, but in general, rarefaction curves tended towards stabilization, suggesting we sampled a representative part of the arboreal community. In the second chapter, several environmental and canopy variables (canopy openness, basal area, rock cover, soil cover, bamboo cover, canopy height and declivity) were correlated to species density through a canonical correspondence analysis. Mean canopy openness and LAI (leaf area index) were compared between wet and dry seasons, and we found significant differences between them. Our results demonstrated that environmental variables, especially rock cover, declivity and canopy openness, were correlated to species density, influencing their distribution along the forest remnant and creating environmental gradients. Climate seasonality in the cerrado imposes environmental pressures to plants, and the presence of intense light during the dry season in deciduous forests seems to be a determinant factor. In general, our results provide important contributions to deciduous forest conservation in central Brazil, demonstrating the influence of environmental variables in natural regeneration of arboreal communities and the importance of this knowledge to management plans and restoration of degraded habitats.